Spectrum of pathogenic variants and high prevalence of pathogenic BBS7 variants in Russian patients with Bardet–Biedl syndrome - Orlova, M.; Gundorova, P.; Kadnikova, V.; Polyakov, A. (Frontiers in Genetics, 2024)
Introduction: Bardet-Biedl syndrome is a rare condition characterized by obesity, retinitis pigmentosa, polydactyly, development delay and structural kidney anomalies. This syndrome has autosomal recessive type of inheritance. For the first time molecular genetic testing has been provided for the large cohort of Russian patients with Bardet-Biedl syndrome.Materials and methods: Genetic testing was provided to 61 unrelated patients using an MPS panel that includes coding regions and intronic areas of all genes (n=21) associated with Bardet-Biedl syndrome as of today.Results: The diagnosis was confirmed for 41% of the patients (n=25). Disease-causing variants were observed in BBS1, BBS4, BBS7, TTC8, BBS9, BBS10, BBS12 and MKKS genes. In most cases pathogenic and likely pathogenic variants were localized in BBS1, BBS10 and BBS7 genes, also in these genes recurrent variants were observed.Discussion: The frequency of pathogenic and likely pathogenic variants in the genes BBS1 and BBS10 among Russian patients matches the research data in other countries. Frequency of pathogenic variants in BBS7 gene is about 1.5-2% patients with Bardet-Biedl syndrome, while in cohort of Russian patients the part is 24%. Also, in BBS7 gene recurrent pathogenic variant c.1967_1968delinsC was detected. The higher frequency of this variant in Russian population, as well as the lack of association of this pathogenic variant with Bardet-Biedl syndrome in other populations suggests that the variant c.1967_1968delinsC in the BBS7 gene is major and has a founder effect in Russian population.Results provided in this article show the significant role of pathogenic variants in the BBS7 gene for patients with Bardet-Biedl syndrome in Russian population.